Perlindungan Hukum Terhadap Pekerja Anak, Kajian Ketentuan United Nations Convention On The Right Of The Child - Lucia Charlotta Octovina Tahamata (SASI, 2018)
The State has the duty and role in protecting and guaranteeing the human rights of its citizens. Violations of human rights often occur against vulnerable groups, one of which is children. Children as vulnerable groups have special rights due to their limitations, so they need protection. Countries in the world agree to review the protection of children by signing and ratifying Convention on the Right of the Child 1989. This Convention specifically regulates the protection and guarantee of the rights of the child to be undertaken by States Parties. However, violations of child rights continue to occur, one of them being child labor. Working causes children to lose their right to grow, grow, play and receive education. Writing method used is normative juridical research, that is by analyzing the legal issues contained in legislation related to the problem under study. The problem approach used by the conceptual approach and the legislative approach, using the source of primary legal material as a reference to complete the writing and collection of legal materials is done by using literature study techniques which are then analyzed through qualitative techniques. The results show that the state should be responsible for child labor under the Convention on the Right of the Child 1989, but the binding force of the rule has not been implemented by the state in accordance with the existing material and conditions. The evidence can be seen from various cases of child rights violations that still occur, such as children who are still employed.